1974
DOI: 10.1111/j.1365-2133.1974.tb15866.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the skin flora of dialysis and transplant patients

Abstract: SUMMARY The skin flora of patients on routine haemodialysis and of outpatients with a renal transplant has been investigated and compared with that of rheumatology outpatients at the same hospital. Dialysis patients had significantly smaller numbers of organisms on the skin. No excess of pathogens or potential pathogens was found in any group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

1975
1975
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…ESRD is a long-standing and chronic disease. In addition, ESRD patients could have retention of urea on the skin and experience drying of the skin due to water withdrawal [27]. Such changes may bring about a shift in skin colonizers.…”
Section: Discussionmentioning
confidence: 99%
“…ESRD is a long-standing and chronic disease. In addition, ESRD patients could have retention of urea on the skin and experience drying of the skin due to water withdrawal [27]. Such changes may bring about a shift in skin colonizers.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies of the microbial flora in the nose and on the skin of hemodialysis patients have examined the presence or absence of gram-negative bacilli. Noble and associates (11) recovered multiple species of gram-negative bacilli from the nose and skin of hemodialysis patients and renal transplant patients, but they did not study the relationship between nose and skin colonization. In the first of two studies published by Goldblum and co-workers (2), they recovered very few gram-negative bacilli from the skin of either hemodialysis patients or normal controls and suggested that failure to culture gram-negative rods from skin in their patients might have been due to the arid climate of New Mexico where the studies were performed.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is supported by other studies that showed that S. aureus carriage rates vary between different ethnic groups, with higher rates in white individuals, in men, and lower rates in elderly individuals (Williams, 1963; Armstrong‐Esther, 1976; Riewerts Eriksen et al , 1995; Parnaby et al , 1996; Cole et al , 2001; Peacock et al , 2003; Herwaldt et al , 2004). Increased carriage rates are found in hospitalized patients (Goslings & Buchli, 1958; Shooter et al , 1958; Williams et al , 1959; Noble et al , 1974; Paul et al , 1982; Kluytmans et al , 1997; Nouwen et al , 2001). Another recently discovered nasal determinant is smoking status: current smoking was negatively associated with nasal S. aureus carriage (van Belkum et al , 2009).…”
Section: Staphylococcus Aureusmentioning
confidence: 99%